A proposal to create an extension to the European baseline series. (1st December 2017) - Wilkinson, Mark; Gallo, Rosella; Goossens, An; Johansen, Jeanne D.; Rustemeyer, Thomas; Sánchez‐Pérez, Javier; Schuttelaar, Marie L.; Uter, Wolfgang
Summary: Background: The current European baseline series consists of 30 allergens, and was last updated in 2015. Objectives: To use data from the European Surveillance System on Contact Allergies (ESSCA) to propose an extension to the European baseline series in response to changes in environmental exposures. Methods: Data from departmental and national extensions to the baseline series, together with some temporary additions from departments contributing to the ESSCA, were collated during 2013–2014. Results: In total, 31689 patients were patch tested in 46 European departments. Many departments and national groups already consider the current European baseline series to be a suboptimal screen, and use their own extensions to it. The haptens tested are heterogeneous, although there are some consistent themes. Potential haptens to include in an extension to the European baseline series comprise sodium metabisulfite, formaldehyde‐releasing preservatives, additional markers of fragrance allergy, propolis, Compositae mix, and 2‐hydroxyethyl methacrylate. Conclusion: In combination with other published work from the ESSCA, changes to the current European baseline series are proposed for discussion. As well as addition of the allergens listed above, it is suggested that primin and clioquinol should be deleted from the series, owing to reduced environmental exposure.